What’s obscure with previtamin D Action Spectrum – a challenge for AI - Terenetskaya Irina (EPJ Web of Conferences)
The article discusses issues related to the significant difference between the Action Spectra of Vitamin D synthesis in vivo and in vitro. Experimental measurements of previtamin D photosynthesis in vitro under the quasy-monochromatic UV radiation at different wavelengths are presented, which indicate that nonlinear kinetics of previtamin D accumulation together with the wavelength effect on its side photoconversions, will lead to ambiguity in the Previtamin D Action Spectrum depending on the accepted erythema dose at which it was measured.